2011
DOI: 10.17221/1544-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium avium subsp. hominissuis infection in two sibling Fjord horses diagnosed using quantitative real time PCR: a case report

Abstract: This report describes new possibilities for intravital and post mortem diagnosis of avian mycobacteriosis in horses using the quantitative real time PCR (qPCR) method. Using this method, Mycobacterium avium subsp. hominissuis was diagnosed in two sibling Fjord horses. In the first horse, M. a. hominissuis was detected by qPCR in numbers of 2.89 × 10 5 and 1.47 × 10 4 cells per 1 g of intestinal content and mesenteric lymph nodes, respectively; in the second horse, faeces and mesenteric lymph node samples showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
(39 reference statements)
0
8
0
Order By: Relevance
“…Ky33 profile has been isolated in European countries, but not isolated in Japan. This profile has been isolated from pig, and cattle in France [25], and pig and chicken in Finland [3]. These inconsistent results may be due to the age of pigs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ky33 profile has been isolated in European countries, but not isolated in Japan. This profile has been isolated from pig, and cattle in France [25], and pig and chicken in Finland [3]. These inconsistent results may be due to the age of pigs.…”
Section: Discussionmentioning
confidence: 99%
“…MAH infection in pigs is characterized by granulomatous lesions in the lymph nodes of the digestive system [3]. Since most pigs do not show any clinical signs of infection, visceral organs, including lesions, are excluded from processing by macroscopic inspection at the slaughterhouse.…”
mentioning
confidence: 99%
“…In available literature, there are no reports of clinicopathological findings associated with the M. bovis infection in horses, but it has been reported that Mycobacterium avium hominissuis (the causative agent of avian mycobacteriosis) infection in horses led to thrombocytosis, hypoalbuminemia, increased serum activities of alkaline phosphatase and lactate dehydrogenase, decreased packed cell volume and presence of band neutrophil in peripheral blood (Blahutkova et al, 2011). M. ulcerans infection in horses led to a mild decrease in the serum levels of sodium, creatinine and inorganic phosphate and increased serum activity of gamma glutamyl transferase (Van Zyl et al, 2010).…”
Section: Tuberculosismentioning
confidence: 99%
“…; Blahutkova et al . ). Mycobacteria have been identified from a liver biopsy of a horse with diarrhoea and weight loss (Lofstedt and Jakowski ).…”
Section: Introductionmentioning
confidence: 97%
“…Molecular identification of mycobacterial agents from diseased intestine using polymerase chain reaction (PCR) is diagnostic (Pavlik et al 2008;Ryhner et al 2009;Keck et al 2010), and serology can also be used to identify a rising antibody titre to mycobacteria (Mair 1996). Intestinal mycobacteriosis manifests as a gastrointestinal syndrome but at post mortem examination the disease is often disseminated (Cline et al 1991;Blahutkova et al 2011). Mycobacteria have been identified from a liver biopsy of a horse with diarrhoea and weight loss (Lofstedt and Jakowski 1989).…”
Section: Introductionmentioning
confidence: 99%